Transgressions in the Pedagogy of Religion – between Instrumentalization and Emancipation of Religious Education - Humeniuk, Monika (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2019)
On the basis of the human interests concept and relevant types of rationality by Jürgen Habermas I reconstructed three models of religious education: confessional, hermeneutic and critical approach. The first of them, confessional approach, grows from the cognition objectivism and the axiological absolutism. The second one, connected with the hermeneutics in a religious education, understands knowledge as a social construct and refers to communication skills in the negotiation meanings. The last one, critical approach, makes emancipation skills, in the areas of debunking and active opposition to an oppression and enslavement coming from ideologisation of religion, the major aim of a religious education. Each one of those models has a different potential of transgression understood as a flexibility towards boundaries of self-understanding. Each of them differently addresses the context of progressive secularisation and socio-cultural pluralism.
Keywords: Habermas, Jürgen (1929- )